Pengaruh Keterampilan Pengelolaan Kelas Terhadap Keaktifan Siswa di Sekolah Dasar - Andika Rizky Nugraha; Evi Setianingsih; Fani Widia Putri; Wahdini Rohmah Jaelani (Journal on Education, 2023)
This study aims to determine the effect of classroom management skills on student activity in elementary schools. This study use the method of literature study. The data were obtained from the results of a review of several journal articles which were then processed into descriptions for the discussion. The results of this study indicate that classroom management is very influential on the activeness of students in class. A teacher who is able to manage the class well will create a conducive classroom environment for active children. Therefore it is very important for teachers to master classroom management skills